Adam Trexler, Anthropocene Fictions: The Novel in a Time of Climate Change - Prorokova, Tatiana (Journal for the Study of Religion, Nature and Culture, 2018)
Adam Trexler, Anthropocene Fictions: The Novel in a Time of Climate Change (Charlottesville and London: University of Virginia Press, 2015), 272 pp., 29.50 (pbk), ISBN: 9-780-81393692-5.